Peningkatan Pemahaman Konsep Operasi Hitung Perkalian dengan Penggunaan Media Saku Perkalian - Liya Indriyani; Ibnu Muthi (Jurnal Pendidikan, Bahasa dan Budaya, 2024)
This Research Is Motivated By Students' Low Understanding Of Mathematical Concepts Which Is Caused By The Learning Process Not Optimizing The Use Of Media When Learning Takes Place In Understanding The Concepts Of Learning Material And Not Giving Students Opportunities To Participate In Learning. This Research Aims To Improve Students' Understanding Of Mathematical Concepts Multiplication Pocket Media Is Able To Provide Details In The Form Of Existing Images, So That Students Are Able To Remember Them Better. Understanding The Concept Of Multiplication Calculation Operations. First, Restate The Concepts That Have Been Studied With The Following Example Questions. 5 X 4 = 4 + 4 + 4 + 4 + 4= 20. Most Students' Work Process Is Not Appropriate Because Students Do Not Re-Express Their Spelling Concepts Directly In The Results. Second, Classifying Objects Based On Mathematical Concepts.